2011
DOI: 10.1159/000321896
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on the Efficacy of Fexofenadine in Seasonal Allergic Rhinitis: A Meta-Analysis of Randomized, Double-Blind, Placebo-Controlled Clinical Trials

Abstract: Rationale: Evidence-based medicine represents the effort to highlight the best intervention for patients, clinicians, and policy makers, each from their respective viewpoint, to solve a particular health condition. According to a recently diffused grading system of evidence and recommendations for medical interventions, efficacy and safety represent 2 of the most important features to consider, and data from meta-analyses of randomized controlled clinical trials (RCTs) is the strongest supporting demonstration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 94 publications
2
29
0
7
Order By: Relevance
“…These guidelines, however, do not discuss non-pharmacological products, probably due to the scarcity of studies of acceptable scientific quality in this context. The degree of symptom reduction in the present study is comparable with a usual result in placebo-controlled studies of nasal steroids and oral antihistamines [17,18]. Hence, considering the complete absence of significant adverse effects and, with a reservation for the huge imbalance in the number of studies performed compared with intranasal steroid treatment, we suggest that this kind of barrier protection may be tried as an early choice in the treatment of SAR, particularly in the mild/moderate stages of the disease, corresponding to the selected contingent in the present study; our inclusion criteria selected cases with mild/moderate disease, and the degree of severity also comprised the majority of patients with allergic rhinitis [4].…”
Section: Discussionsupporting
confidence: 89%
“…These guidelines, however, do not discuss non-pharmacological products, probably due to the scarcity of studies of acceptable scientific quality in this context. The degree of symptom reduction in the present study is comparable with a usual result in placebo-controlled studies of nasal steroids and oral antihistamines [17,18]. Hence, considering the complete absence of significant adverse effects and, with a reservation for the huge imbalance in the number of studies performed compared with intranasal steroid treatment, we suggest that this kind of barrier protection may be tried as an early choice in the treatment of SAR, particularly in the mild/moderate stages of the disease, corresponding to the selected contingent in the present study; our inclusion criteria selected cases with mild/moderate disease, and the degree of severity also comprised the majority of patients with allergic rhinitis [4].…”
Section: Discussionsupporting
confidence: 89%
“…Oral antihistamines are frequently used in case of allergic comorbidities such as rhinitis and are used in almost one‐third of the patients with ocular symptoms . Drugs such as loratadine, desloratadine, and fexofenadine are highly effective for the treatment of allergic rhinoconjunctivitis (ARC) (Table ). Most of the SRs have addressed total symptoms scores, without evaluating impact on specific ocular symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore participants received pharmacological treatment for rhino-conjunctivitis according to the Japanese Guidelines for Allergic Rhinitis21 without limitations except for oral corticosteroids in addition to OIT. Many RCTs have shown that antihistamines (Levocetirizine hydrochloride, Fexofenadine hydrochloride), nasal steroid sprays (Mometasone furoate, Fluticasone furoate), ocular antihistamine drops (Ketotifen fumarate, Olopatadine hydrochloride) and ocular steroid drops (Fluorometholone) used as rescue medications improve rhino-conjunctive symptoms for pollinosis27282930. Thus, the rhino-conjunctive symptoms in the placebo and active groups may have been suppressed to the same extent by rescue medications.…”
Section: Discussionmentioning
confidence: 99%